Hepatitis E: New Clinical and Public Health Problem on the Western World? Review - Roberto Focaccia (Archives of Hepatitis Research - Peertechz Publications, 2017)
Until recently, the occurrence of Hepatitis E in the western hemisphere did not amount to a clinical  concern, due to its benign and usually sub-clinical evolution, as opposed to Asia and Africa, where large epidemies with high levels of lethality occur. More sensible diagnostic exams have shown a high prevalence of the infection through genotype 3 in the eastern hemisphere, with reports of hepatic infection, cirrhosis, and extremely severe systemic [1-3] and neurological extra-hepatic manifestations, especially on immunosuppressed patients [4- 6]. Hepatitis E: an emerging infection in developed countries [7], suggesting the occurrence of a new and important clinical and public health problem [3,8].